Moderasi Beragama Perspektif Hasbi Ash-Shiddieqy, Hamka, dan Quraish Shihab - Muhammad Ulinnuha; Mamluatun Nafisah (SUHUF, 2020)
This paper departs from the problem of misinterpretation of religious texts that need to be traced sociologically and historically into Indonesian Islamic scientific literature, particularly the Qur’anic Exegesis literature. Further this writing tries to look for the middle path or even as an anti-thesis to those misinterpretations. To know the thought of Hasbi Ash-Shiddieqy, that of Hamka, and that of Quraish Shihab on religious moderation, the author uses a historic-sociological approach. The result of this study concludes that their conception in general can be described as follows: First, from the aspect of definition, Hasbi Ash-Shiddieqy, Hamka, and Quraish Shihab have interpreted religious moderation comprehensively. Second, there are seven dimensions of religious moderation being supplemented by its indicators namely moderation in the aspects of theology, that of worship, that of relationship (mu’amalah), that of law, that of creation of man and the universe, and that of the government and culinary. These seven dimensions of moderation are highly relevant to the context of Indonesian society which is maritime, plural, heterogeneous as well as multiethnic, linguistic and religious. Key words: Moderation, Hasbi Ash-Shiddieqy, Hamka, Quraish Shihab.